2020
DOI: 10.1007/s11282-020-00465-8
|View full text |Cite
|
Sign up to set email alerts
|

The practice of oral and maxillofacial radiology during COVID-19 outbreak

Abstract: The current coronavirus disease 2019 (COVID-19) outbreak has brought substantial challenges to the world health system, including the practice of dental and maxillofacial radiology (DMFR). DMFR will carry on an imperative role in healthcare during this crisis. This rapid communication has collected and evaluated all the best current evidence and published guidelines as well as professional recommendations to help maxillofacial radiologists and dental practitioners for safer radiological and imaging examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 14 publications
0
29
0
10
Order By: Relevance
“…Although, some institutions/clinics are still practising paper. It is preferable to have a separate room outside the operatory room for the purpose of storing dental records [ 56 ]. Storage and strategic stockpiling: Researchers have stated that SARS CoV-2 can remain alive on environmental surfaces varying from few hours to days [ 57 ].…”
Section: Dental Radiology and Covid-19mentioning
confidence: 99%
See 4 more Smart Citations
“…Although, some institutions/clinics are still practising paper. It is preferable to have a separate room outside the operatory room for the purpose of storing dental records [ 56 ]. Storage and strategic stockpiling: Researchers have stated that SARS CoV-2 can remain alive on environmental surfaces varying from few hours to days [ 57 ].…”
Section: Dental Radiology and Covid-19mentioning
confidence: 99%
“…The dental radiology stock including radiographs and processing solutions are stored in an air-tight plastic container, which makes them easy for disinfection and storage. It has been reported that SARS CoV-2 can stay viable on plastic containers for up to three days, therefore it is advised to abstain from touching for the same number of days [ 56 ]. The consumption of stock should follow the concept of first-in, first-out, (FIFO), wherein the oldest stock is taken out first for consumption.…”
Section: Dental Radiology and Covid-19mentioning
confidence: 99%
See 3 more Smart Citations